Analysis of Numeracy Literacy Skills Based on Gender of Second-Grade Elementary School Students - Yuliani Yuliani; Muhammad Turmuzi; Baiq Yuni Wahyuningsih; Aulia Usman (Yayasan Insan Mulia Bima, 2026)
This study aims to describe in depth the numeracy literacy skills in number concepts from a gender perspective among second-grade students at SD Negeri 1 Selebung in the 2025/2026 academic year. The approach used in this study is a mixed-methods design with a sequential explanatory approach. The research population comprised all 26 second-grade students. The qualitative sample was determined using a purposive sampling technique, consisting of 6 subjects selected based on the representation of their cognitive competence levels. Data collection was carried out through test instruments, interviews, and documentation. The validity of the quantitative data was ensured through expert judgment, while the qualitative data was verified via technical triangulation and member checking. Quantitative data analysis utilized descriptive statistics, whereas qualitative data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The quantitative results revealed a significant disparity in achievement, where female students achieved a higher mean score of 91.66 (with 91.66% categorized in the Proficient level and 1 person student in the proficient category (8.33%), while male students obtained a mean score of 77.85 (50% Proficient, 42.85% Competent, and 7.14% Basic), demonstrating a score gap of 13.81 points. The qualitative analysis further confirmed that this disparity was influenced by psychological traits and learning habits. Female students upervised study patterns at home. Conversely, male students exhibited impulsive tendencies, lacked meticulousness during testing, and preferred to spend their free time on playtime activities without revising their lessons.